AB0483 Risk Factors Associated with Greater Damage in Systemic Lupus Erythematosus Patients: An Egyptian Multicenter Study. (15th July 2016) - Eissa, M.; Hammad, M.; Fathi, S.
Abstract : Background: Systemic lupus erythematosus (SLE) is a prototypic multisystem autoimmune disorder. The total damage in a patient with SLE may result from SLE itself or any other pathologic process. The management of SLE targets immediate control of disease activity, but also it should include the prevention of organ damage from treatment and comorbidity by minimizing or controlling risk factors of organ damage. Objectives: The aim of this study was to assess risk factors of greater damage in a sample of Egyptian SLE patients. Methods: This is an Egyptian multicenter retrospective study. The study included 100 SLE patients: 64 patients from Cairo University Hospital and 36 patients from Zagazig University Hospital. The patients are classified according to the Systemic Lupus International Collaborative Clinics (SLICC) criteria for SLE. Systemic Lupus International Collaborative Clinics/ACR Damage Index (SLICC/ACR-DI) was used to measure damage in each patient. The period of data collection took 4 months. The collected data included demographic, clinical, serologic data and medications. Results: 100 SLE patients (93% females and 7% males with mean age 33.44±8.6 and disease duration 6.25 (1–17) were included. The most frequent item in the damage index in our patients was retinal changes or optic atrophy (12%), followed by osteoporosis (11%). The total SLICC/ACR Damage Index Score ranged from 0 to 8. There was a significant positive correlation between the Damage Index and the patient's age, SLEDAI-2k at the onset and at the last visit (P<0.05). A higher Damage Index score was found in hypertensive patients compared to normotensive patients and among those with positive anti-phospholipid antibodies compared to those with negative anti-phospholipid antibodies and the difference was statistically significant (P<0.01). A statistically significant higher Damage Index score was found in cyclophosphamide users compared to non-users, and in those with proteinuria & seizures compared to those without (P<0.05). Comparing all variables; seizures was by far the most important predictor of Damage Index in the regression model (Beta=0.279, P=0.028), followed by SLEDAI at last visit (Beta =0.234, P=0.062) and then Antiphospholipid Syndrome (Beta =0.335, P=0.064). Conclusions: Damage in SLE cannot be prevented completely as SLE is an aggressive disease treated by aggressive medications. Frequent ophthalmologic follow up is necessary for all SLE patients. SLE patients with hypertension and positive antiphospholipid antibodies develop higher damage scores so they need closer observation and control of these factors if possible. Rheumatologists should try to minimize damage as much as possible to maintain patients' health, functioning, and general wellbeing. Disclosure of Interest: None declared